Experimental and Numerical Study on Damage Characteristics of Web Frame Structure Under Conical Impact - Zhengjie Li; Caixia Jiang; Gaofei Wang; Nan Zhao; Yue Lu; Kun Liu (Journal of Marine Science and Engineering)
This paper investigates the dynamic performance of web frame structures under the impact of a conical hammer head. Compared with existing research on flat plates and stiffened panels, web frame structures exhibit significant differences in load-bearing mechanisms and design principles. To address these limitations, a series of drop-weight impact tests under different impact conditions are conducted, and the effects of drop heights on the dynamic responses of the web frame structure are systematically analyzed. By measuring the impact force responses and damage shapes, nonlinear dynamic characteristics and damage modes of the web frame structures under conical hammer head impacts can be revealed. The results indicate that higher drop heights lead to more severe damage areas, and damage area is more concentrated in the contact area of the indenter. Meanwhile, the peak impact force increases from 429.06 MN to 606.62 MN as the drop height increases from 1 m to 2.5 m, indicating a 41.38% rise. Additionally, the maximum energy absorbed by the structure reaches 62.89 KJ, and the energy loss ratio ranges from 18.58% to 30.73%. The findings offer critical theoretical insights and technical support for the optimization of impact resistant designs in web frame structures.